Event management system for ponggal night charity show - Kalai, Vani Arivalacan (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The event management industry has grown tremendously in the last 50 years as events are no longer held exclusively in big cities. Ponggal Night Charity Show is an event organized by UNIMAS Indian student with the cooperation of others due to Ponggal festival which is celebrated by Indian community as a harvest festival. Without a proper computerized system, the committee is having difficulties in managing the event in a systematic manner. In order to deal with the big amount of audience, the organizing group had problems in the process of ticket selling especially according to the seat and table number. It is hard to explain about the table arrangements and seating procedures that has been arranged by manual sketching. To overcome these difficulties, a system has been proposed which called Event Management System for Ponggal Night Charity Show. This system provides online ticket booking, information gathering and feedback. Moreover, this web based system also contains more details about the content of "Ponggal Night Charity Show" event, food and beverage provided charity details and also ticket availability. Besides that, this system also will provide a systematic way of communicating among the management team who really need to consult each other for most of the tasks given to them. Through this system, they can easily discuss among themselves about the progresses and tasks just by posting it on the forum provided.